Does muscle stiffness predict early-onset knee osteoarthritis? - Gökşen, Ayşenur; Can, Filiz; Yılmaz, Seval (Journal of Surgery and Medicine, 2021)
Background/Aim: The precise evaluation of the surrounding soft tissues and documenting it by clinical measurements are extremely important for detecting early-stage knee osteoarthritis (OA). Shear wave ultrasound elastography is the latest technology that directly measures the mechanical properties of a tissue, including muscle stiffness. This study was planned to investigate the relationship between Rectus Femoris (RF) and Biceps Femoris (BF) muscle stiffness and the relevant symptoms observed in OA. Methods: Thirty-one patients including 21 females and 10 males between 45-67 years of age, diagnosed with early-stage knee OA and 10 healthy individuals were included in this prospective case-control study. Both RF and BF muscle stiffness were evaluated by shear wave elastography (SWE), and the knee range of motion was calculated by a goniometer. The pain intensity was measured by the Visual Analogue Scale (VAS), knee function, with the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and functional performance, using the 6-minute walk test and the step-climbing test. Results: There was a positive correlation between BF muscle stiffness and WOMAC stiffness (P=0.014, r=0.446). There was no difference in Rectus Femoris and Biceps Femoris muscle stiffness between the osteoarthritis patients and healthy individuals (P=0.11 and P=0.10, respectively). Conclusion: It can be concluded that the symptom of stiffness seen in early-stage knee OA is caused by BF muscle spasm related to the flexor reflex.